(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
The study aimed at estimating the repeatability of growth traits and principal components of body size (PC1) of crossbred Nigerian local chickens using 5 biweekly records. A total of 123, 49, 116, 137, 42, and 64 chickens of Isa Brown × frizzle feathered (IB×F), Isa Brown × naked neck (IB×Na), Isa Brown × normal feathered (IB×N), frizzled feathered × Isa Brown (F×IB), naked neck × Isa Brown (Na×IB), and normal feathered × Isa Brown (N×IB) genotypes, respectively, were produced at day-old in 12 hatches. Data were taken on body weight (BWT), linear body measurements, and PC1 at 2, 4, 6, 8, and 10 weeks from each individual. The repeatability of body weight (0.27 to 0.49) for the six genotypes was moderately high. Repeatability of PC1 (0.54) was only high in the IB×F genotype. Repeatability of the linear body measurements was high (0.49-0.67), especially in IB×N and N×IB genotypes. The expected relative genetic gain indicated that fewer than 5 records were enough to estimate the repeatability of these traits. It was concluded that considerable genetic improvement in the lifetime average body size of IB×N, N×IB and IB×F genotypes could be realized using fewer than 5 records of the growth traits and PC1 with high repeatability estimates as selection criteria.